2004
DOI: 10.1002/anie.200353433
|View full text |Cite
|
Sign up to set email alerts
|

A Polyoxometalate Containing the {Ni2N3} Fragment: Ferromagnetic Coupling in a NiII μ‐1,1 Azido Complex with a Large Bridging Angle

Abstract: Dedicated to Professor M. T. Pope on the occasion of his 70th birthday.The chemistry of polyoxometalates (POMs) continues to attract much attention, particularly with respect to potential catalytic activity. [1] In the last few years it has also been noted that POMs are ideal models for the study of exchange interactions in magnetic clusters, as they represent a class of well-insulated complexes of controlled nuclearity and topology.[ [5] and that N 3 À is certainly one of the most interesting magnetic couple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(24 citation statements)
references
References 32 publications
1
23
0
Order By: Relevance
“…[8] Recently, insertion into paramagnetic polyoxometalate matrices of exogenous ligands and especially that of the azido anion [9] has shown that such polydentate ligands can also allow the assembly of magnetic polyoxometalate subunits, [10] but in addition could impose ferromagnetic interactions within the cluster. [11,12] Co II polyoxometalate compounds containing from two to nine interacting paramagnetic centers have been reported.…”
Section: A C H T U N G T R E N N U N G [(A-a-siw 9 O 34 )A C H T U N mentioning
confidence: 99%
“…[8] Recently, insertion into paramagnetic polyoxometalate matrices of exogenous ligands and especially that of the azido anion [9] has shown that such polydentate ligands can also allow the assembly of magnetic polyoxometalate subunits, [10] but in addition could impose ferromagnetic interactions within the cluster. [11,12] Co II polyoxometalate compounds containing from two to nine interacting paramagnetic centers have been reported.…”
Section: A C H T U N G T R E N N U N G [(A-a-siw 9 O 34 )A C H T U N mentioning
confidence: 99%
“…Interestingly, we have shown that the synthesis of POM/N 3 À complexes leads to azido compounds characterized by original structural features that differ from those obtained using organic ligands. Complexes with very large [11] or very small [17] M-(N 3 )-M angles have been isolated, as well as a unique Cu II complex in which a m-1,1,1,3,3,3-azido ligand assembles a nine-paramagneticcenter cluster. [17] In this paper, we present the synthesis, X-ray crystal structure analysis, and [17] (2 b) compound, determined by a multifrequency HF-EPR study, and the results are compared and discussed.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have initiated the study of magnetic POM compounds in which the paramagnetic transition-metal ions are connected by azido ligands. [11] For more than two decades, azido-bridged transition-metal complexes have inspired a lot of experimental and theoretical work. [12] It has been established that the end-to-end coordination mode tends to lead to antiferromagnetic coupling, while the end-on coordination generates ferromagnetic coupling.…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that an end-on coordination mode is adopted by the N 3 À ion. [5] implying that isomerization occurred during the formation of 1 a; such a process has been previously observed. Indeed, Kortz et 12À species.…”
mentioning
confidence: 81%